Designing an arm support model to minimize UECTD risk among Filipino electronic technicians using QFD, KANO model, TRIZ and anthropometry - Indardaya, Abdulah P. (College of Engineering, University of the Philippines Diliman, 2014)
Electronics technicians are prone to develop Upper Extremity Cumulative Trauma Disorder (UECTD) owing to the awkward posture, repetitive motion and static loading associated with the routine tasks of multi-testing, soldering and desoldering. In the Philippines, validation using Rapid Upper-Limb Assessment (RULA) yielded a score of 5.774 requiring intervention as a result of an Action Level 3 classification. A two-phase study approach, Quality Functional Deployment (QFD), KANO model, Theory of Inventive Problem Solving (TRIZ) and Anthropometry results were used as inputs in the design stage. QFD revealed 168 relationships between engineering and customer requirements, and 48 correlations with technical requirements. KANO model analysis gauged how the engineering attributes of the arm support design were perceived by the technicians and their potential effect on satisfaction. Consequently, six "attractive", five "one-dimensional" and three "indifferent" engineering attributes were generated. Meanwhile, contradictions determined from QFD correlation analyses were resolved using TRIZ. The resulting engineering attributes based on QFD, KANO and TRIZ were matched with the 5th to 95th percentile upper extremity anthropometric dimensions to determine the best fit and the ensuing optimal attributes were used to construct the design model. This study demonstrated the effectiveness of combining TRIZ, QFD principles, KANO Model Analysis, and Anthropometry in achieving the target ergonomic and functional design objectives tailored after user requirements to mitigate a real-world occupational hazard.